2000
DOI: 10.1002/(sici)1097-4547(20000601)60:5<613::aid-jnr6>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase induction in astroglial cell cultures: Effect on heat shock protein 70 synthesis and oxidant/antioxidant balance

Abstract: Glial cells in the nervous system can produce nitric oxide in response to cytokines. This production is mediated by the inducible isoform of nitric oxide synthase. Radical oxygen species (ROS) and nitric oxide (NO) derivatives have been claimed to play a crucial role in many different processes, both physiological such as neuromodulation, synaptic plasticity, response to glutamate, and pathological such as ischemia and various neurodegenerative disorders. In the present study we investigated the effects of NO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 39 publications
1
64
0
Order By: Relevance
“…On the other hand, microglial cells may try to attenuate neuronal injury by removing cell debris. Our earlier studies have demonstrated the ability of astrocytes to respond to pro-inflammatory cytokines, which stimulate transcription factors and cause induction of a number of genes, including inducible nitric oxide synthase (iNOS) (29)(30)(31), cyclooxygenase-2 (COX-2) (32) and secretory phospholipase A 2 (sPLA 2 ) (29,33,34). Increase in PLA 2 has been regarded as an important factor underlying a number of neurodegenerative diseases and PLA 2 inhibitors have been shown to protect against neurotoxicity induced by oxidative stressors (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, microglial cells may try to attenuate neuronal injury by removing cell debris. Our earlier studies have demonstrated the ability of astrocytes to respond to pro-inflammatory cytokines, which stimulate transcription factors and cause induction of a number of genes, including inducible nitric oxide synthase (iNOS) (29)(30)(31), cyclooxygenase-2 (COX-2) (32) and secretory phospholipase A 2 (sPLA 2 ) (29,33,34). Increase in PLA 2 has been regarded as an important factor underlying a number of neurodegenerative diseases and PLA 2 inhibitors have been shown to protect against neurotoxicity induced by oxidative stressors (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Increase in Hsp70 protein expression was also found after treatment of cells with the NO generating compound sodium nitroprusside (SNP), thus suggesting a role for NO in inducing Hsp70 proteins. The molecular mechanisms regulating the NO-induced activation of heat-shock signal seems to involve cellular oxidant/antioxidant balance, mainly represented by the glutathione status and the antioxidant enzymes [20,21,28]. Induction of Hsp72 under stress conditions is often accompanied by the induction of other heat-shock proteins, as recently shown by Sultana et al [35] using b-amyloid as a model of neurotoxicity.…”
Section: Redox Regulation Of Gene Expressionmentioning
confidence: 97%
“…Under normal conditions, Nrf2 is sequestered in the cytoplasm by an actin-binding protein, Kelch-like ECH associating protein 1 (Keap1), but upon exposure of cells to oxidative stress Nrf2 dissociates from Keap1, translocates to the nucleus, binds to antioxidant responsive elements (AREs), and activates HO-1 gene one of the end products of heme degradation by heme oxygenase, protects against the cytotoxic effects caused by strong oxidants H 2 O 2 and ONOO- [18]. The conception that NO and RNS can be directly involved in the modulation of HO-1 expression in eukaryotes is based on the evidence that different NO-releasing agents can markedly increase HO-1 and Hsp70 in a variety of tissues, including brain cells [19,20]. In rat glial cells, treatment with lipopolysaccaride (LPS) and interferon-c (IFN-c) promotes a rapid increase in both iNOS expression and nitrite levels followed by enhancement of Hsp70 [3,20], whereas the modulation of HO-1 mRNA expression by iNOS-derived NO following stimulation with LPS has also been reported in different brain regions, particularly in the hippocampus and substantia nigra in an in vivo rat model of septic shock [19].…”
Section: Redox Regulation Of Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increase in HSP70 protein expression was also found after treatment of cells with the NO generating compound sodium nitroprusside (SNP), thus suggesting a role for NO in inducing HSP70 proteins. The molecular mechanisms regulating the NO-induced activation of a heat shock signal seems to result from cellular oxidant/antioxidant balance, regulated by the glutathione status and the antioxidant enzymes [25][26][27]. With curcumin supplementation, significant decrease in the NO activity was observed when compared to Al treated animals though values were still high in mid brain region in comparison to normal controls.…”
Section: Discussionmentioning
confidence: 99%